Effect of psychological stress on the oral-gut microbiota and the potential oral-gut-brain axis. (November 2022) - Paudel, Durga; Uehara, Osamu; Giri, Sarita; Yoshida, Koki; Morikawa, Tetsuro; Kitagawa, Takao; Matsuoka, Hirofumi; Miura, Hiroko; Toyofuku, Akira; Kuramitsu, Yasuhiro; Ohta, Tohru; Kobayashi, Masanobu; et al.
Abstract: Psychological stress in a chronic course is implicated in various diseases, such as coronary artery disease, diabetes, ulcerative colitis, and psychosomatic pain disorders. Commensal microbiota in the host tissues interact with each other and maintain overall health. Oral and gut microbiomes are considered as the most ecologically rich and taxonomically diverse microbiota communities in humans. The effects of psychological stress on the gut microbiome have been well documented, and the interaction is commonly referred as the microbiota-gut-brain axis. Like the gut microbiome, the oral microbiome contributes to maintaining both local and systemic health. Although the effects of psychological stress on the oral microbiome have been studied, comprehensive knowledge about the oral-brain axis is lacking. The oral cavity and gut can communicate with each other through the microbiota. Three-way interactions within the oral-gut-brain microbiota might exist in patients with psychological stress and disorders. The effect of psychological stress on the gut and oral microbiomes, and the potential interactions within the oral-gut-brain axis are discussed in this review.